K. Sello Duiker's realism: form, critique, and floating kingdoms - Rourke, Warren Jeremy (Department of English Language and Literature, 2018)
Before drawing together composite elements from his works of novelistic art, as well as his life in writing, the intention of this thesis is to argue that Duiker's realism is an 'authentic' one. Furthermore, Duiker's 'commitment' as an authentic literary realist is to 'articulate' an oppositional world outlook that I am codifying as 'alter-native'. The alter-nativism is expressed not only by the 'interplay' of the 'lumpen' protagonists of the novels but by Duiker himself in the extra-generic marginalia to his short literary career. In order to give 'value' to the contention of this thesis as a whole I will utilize a number of theorists working critically with the relation between language and consciousness, and therefore, as I argue, the 'zero point' of social being.